Chlamydia pneumoniae Clinical Isolate from Gingival Crevicular Fluid: A Potential Atherogenic Strain - Filardo, Simone; Di Pietro, Marisa; Schiavoni, Giovanna; Minniti, Gianluca; Ortolani, Emanuela; Romano, Silvio; Sessa, Rosa (Frontiers in Cellular and Infection Microbiology, 2015)
Chlamydia pneumoniae has been associated to atherosclerotic cardiovascular diseases. The aim of our study was to characterize, for the first time, a C. pneumoniae strain isolated from the gingival crevicular fluid of a patient with chronic periodontitis, described as a risk factor for cardiovascular diseases. C. pneumoniae isolate was characterized and compared to the respiratory AR-39 strain by VD4-ompA genotyping and by investigating the intracellular growth in epithelial and macrophage cell lines and its ability to induce macrophage-derived foam cells. Inflammatory cytokine levels were determined in the gingival crevicular fluid sample. C. pneumoniae isolate showed a 99% similarity with the AR-39 strain in the VD4-ompA gene sequence and shared a comparable growth kinetic in epithelial cells and macrophages, as evidenced by the infectious progeny and by the number of chlamydial genomic copies. C. pneumoniae isolate significantly increased the number of foam cells as compared to uninfected and LDL-treated macrophages (45 vs. 6%, P = 0.0065) and to the AR-39 strain (45 vs. 30%, P = 0.0065). Significantly increased levels of interleukin 1-β (2.1 ± 0.3 pg/μL) and interleukin 6 (0.6 ± 0.08 pg/μL) were found. Our results suggest that C. pneumoniae may harbor inside oral cavity and potentially be atherogenic, even though further studies will be needed to clarify the involvement of C. pneumoniae in chronic periodontitis as a risk factor for cardiovascular diseases.